2005
DOI: 10.1590/s1415-47572005000500016
|View full text |Cite
|
Sign up to set email alerts
|

Esterase profile in a pyrethroid-resistant Brazilian strain of the cattle tick Boophilus microplus (Acari, Ixodidae)

Abstract: The cattle tick Boophilus microplus causes great damage in livestock and is considered one of the most important tropical ectoparasites. The traditional method of control is based on the intensive use of pesticides, however the indiscriminate use of these compounds over the years has led to the selection of resistant ticks. Hydrolases, particularly esterases (EST), have been reported to be associated with acaricide resistance in B. microplus. We compared the esterase profile of susceptible and cypermethrin-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 20 publications
0
7
2
Order By: Relevance
“…Using copper sulphate, the intensity of all the esterase bands was similar to those observed in control without inhibitor, thus confirms the absence of arylesterases among the resolved bands. Although Baffi et al (2005) reported EST-3 as carboxylesterase after getting significant inhibition using both malathion and PMSF, in the present study, the staining intensity of EST-3 was inhibited using PMSF but was resistant to both malathion and eserine sulphate. Since EST-2 was inhibited by eserine sulphate, malathion and partially by TPP while EST-1 strongly by PMSF and partially by eserine sulphate and malathion both EST-1 and EST-2 were classified as acetylcholinesterase.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Using copper sulphate, the intensity of all the esterase bands was similar to those observed in control without inhibitor, thus confirms the absence of arylesterases among the resolved bands. Although Baffi et al (2005) reported EST-3 as carboxylesterase after getting significant inhibition using both malathion and PMSF, in the present study, the staining intensity of EST-3 was inhibited using PMSF but was resistant to both malathion and eserine sulphate. Since EST-2 was inhibited by eserine sulphate, malathion and partially by TPP while EST-1 strongly by PMSF and partially by eserine sulphate and malathion both EST-1 and EST-2 were classified as acetylcholinesterase.…”
Section: Discussioncontrasting
confidence: 83%
“…Among the bands detected in Tuxpan and Coatzacoalcos strains, the carboxylesterase, EST-9 and EST-10, respectively, were reported to be responsible for the Kunz and Kemp (1994), Jonsson and Hope (2007); Lovis et al (2013) development of resistance (Jamroz et al 2000). On the contrary, four esterase bands were found in cypermethrin and deltamethrin resistant adult ticks and three esterase bands in the susceptible adult ticks (Baffi et al 2005(Baffi et al , 2008. Similar profiles in resistant larval homogenate (IVRI-IV) were observed in the present study when stained with both anaphthyl and b-naphthyl acetate.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Four classes of esterases are distinguished using this scheme: (i) acetylesterases, which are not affected by any of the aforementioned inhibitors and have a preference for aliphatic substrates related to acetic acid, (ii) arylesterases, which are inhibited by sulphydryl reagents and have a preference for aromatic substrates, (iii) carboxylesterase, which are inhibited by organophosphorus compounds and have a preference for aliphatic esters (typically having a chain longer than acetic acid), and (iv) cholinesterases, which are simultaneously inhibited by OPs and eserine sulphate and have a preference for charged substrates (e.g., choline esters) instead of aliphatic and/or aromatic esters (Oakeshott et al 1993). As an alternative functional criterion beyond those proposed above, these inhibition tests for the biochemical characterisation of esterases have been used to classify a variety of esterases, including those in insects of the genera Culex, Drosophila (Healy et al 1991, Oakeshott et al 1993 and Aedes (Lima-Catelani et al 2004) as well as esterases of Arachnids, such as Rhipicephalus (Boophilus) microplus (Baffi et al 2005), and plants (Carvalho et al 2003).…”
Section: Enzyme Commission 1978 -mentioning
confidence: 99%